2013
DOI: 10.1631/jzus.b1200211
|View full text |Cite
|
Sign up to set email alerts
|

Improved cadmium uptake and accumulation in the hyperaccumulator Sedum alfredii: the impact of citric acid and tartaric acid

Abstract: Abstract:The elucidation of a natural strategy for metal hyperaccumulation enables the rational design of technologies for the clean-up of metal-contaminated soils. Organic acid has been suggested to be involved in toxic metallic element tolerance, translocation, and accumulation in plants. The impact of exogenous organic acids on cadmium (Cd) uptake and translocation in the zinc (Zn)/Cd co-hyperaccumulator Sedum alfredii was investigated in the present study. By the addition of organic acids, short-term (2 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…In addition, tartaric and oxalic acid chelated the heavy metal ions which are detrimental to plants (Li et al 2007). Our results also illustrated that tartaric acid and oxalic acid were increased after GB application and were correlated with the heavy metal stress tolerance in perennial ryegrass (Lu et al 2013). Organic acids excreted by roots could reduce the bio-availability of Cd, and protect the roots from toxicity effects (Liao and Xie 2004;Schwab et al 2005).…”
Section: Discussionmentioning
confidence: 58%
“…In addition, tartaric and oxalic acid chelated the heavy metal ions which are detrimental to plants (Li et al 2007). Our results also illustrated that tartaric acid and oxalic acid were increased after GB application and were correlated with the heavy metal stress tolerance in perennial ryegrass (Lu et al 2013). Organic acids excreted by roots could reduce the bio-availability of Cd, and protect the roots from toxicity effects (Liao and Xie 2004;Schwab et al 2005).…”
Section: Discussionmentioning
confidence: 58%
“…In a study on Brassica napus plants in water culture, it was found that citrate application at a concentration of 2.5 mM in medium containing 10 or 50 µm Cd contributed to the 1.5-times increase in the accumulation of Cd in roots, stems, and leaves of canola (Ehsan et al, 2014). Stimulation of Cd accumulation under the effect of exogenous citrate (but not tartrate) was shown for Cd/Zn hyperaccumulator Sedum alfredii (Lu et al, 2013) and for Spinacia oleracea plants (Degryse, Smolders, and Parker, 2006).…”
Section: Plant Sciencementioning
confidence: 99%
“…Durrett, Gassmann, and Rogers (2007) emphasize that citrate plays a role in the chelation of Fe 2+ during the transport of these ions in the xylem, while FRD3 mediates the efflux of citrate to the root vessels to maintain the transfer of iron to the shoot. Data have been presented on joint xylem transport of Cd and citrate for Zn/Cd hyperaccumulator Sedum alfredii, which increases the transfer and accumulation of Cd in the leaves (Lu et al, 2013).…”
Section: The Involvement Of Organic Acids In Transport and Internal Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Phytoremediation is the process of using trees, shrubs, and grasses to de-contaminate soil and water, and is considered to be a promising, cost-effective solution to heavy-metal pollution (Licht and Isebrands, 2005;Vangronsveld et al, 2009;Xing et al, 2012;Lu et al, 2013). Generally, phytoremediation and especially phytoextraction rely on plants known as hyperaccumulators; however, these are species that often have a low biomass and slow growth rate, leading to a long time periods required for metal removal (Tanhan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%